2019
DOI: 10.1038/s41598-019-54089-y
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical H-ZSM5 zeolites based on natural kaolinite as a high-performance catalyst for methanol to aromatic hydrocarbons conversion

Abstract: The present work introduces a good prospect for the development of hierarchical catalysts with excellent catalytic performance in the methanol to aromatic hydrocarbons conversion (MTA) process. Hierarchical H-ZSM5 zeolites, with a tailored pore size and different Si/Al ratios, were synthesized directly using natural kaolin clay as a low-cost silica and aluminium resource. Further explored for the direct synthesis of hierarchical HZSM-5 structures was the steam assisted conversion (SAC) with a cost-effective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…The industrial flue gas usually consists of N 2 and CO 2 in a volume ratio of 9:1. 51 The selective adsorption capacity of CO 2 /N 2 is calculated by the following equation = S q q p p / / i j i j (9) where q is the adsorption quantity (mmol/g) at the partial pressure p (bar), i represents CO 2 , and j represents N 2 or O 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The industrial flue gas usually consists of N 2 and CO 2 in a volume ratio of 9:1. 51 The selective adsorption capacity of CO 2 /N 2 is calculated by the following equation = S q q p p / / i j i j (9) where q is the adsorption quantity (mmol/g) at the partial pressure p (bar), i represents CO 2 , and j represents N 2 or O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In terms of silicon sources, ZSM-5 was mostly synthesized from chemical silicon sources, such as tetraethyl orthosilicate . To reduce the synthesis cost and protect the environment, it was found that kaolin and rice husk in the waste are rich in silicon, and the calcined rice husk ash (RHA) is rich in SiO 2 . Due to the low packing density of RHA, disposal in landfills or open spaces may cause serious problems related to the environment and human health .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several studies have focused on olefin removal from aromatic streams by clay, and they increased clay's lifetime with the production of a new type of catalyst by clay 1,7,16,42,44,45 . There are other related studies in field, all with high costs for developing catalysts 46‐49 . In the second section of the current study, a new process arrangement is introduced by reusing deactivated clay to increase clay's longevity.…”
Section: Introductionmentioning
confidence: 98%
“…1,7,16,42,44,45 There are other related studies in field, all with high costs for developing catalysts. [46][47][48][49] In the second section of the current study, a new process arrangement is introduced by reusing deactivated clay to increase clay's longevity.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, taking into account the environmental, economic, and abundances in nature, the use of natural resources as alternative precursors can be a distinct added value. It has been studied the success of zeolite synthesis from alternative resources, for example, ka-olin [14,15], rectorite with diatomite [16], and a combination of Indonesia zeolite and kaolin [17]. In this work, the ZSM-5 catalyst was synthesized using the alternative precursor, i.e.…”
Section: Introductionmentioning
confidence: 99%